Konsep Ilmu dan Dua Tingkat Klasifikasinya Menurut Ibn Sina - Wawan Kurniawan (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2022)
The classification of the sciences is one of important topics in the Islamic intellectual history and has attracted the attention of philosophers, historians and even theologians, the great philosopher and polymath Abū ‘Alī Ibn Sina being no exception. However, despite some past studies which either focuses only to one or two works of Ibn Sina or else provides only a general description, still there are some lacunae regarding Ibn Sina’s classification of the sciences. In this article, the author is going to analyze historically and systematically two aspects of the topic: (1) Ibn Sina’s definition of science, and (2) Ibn Sina’s ‘primary’ and ‘secondary’ classification of the sciences. As for the sources, the analysis will be based on five Ibn Sina’s works that are representative of his early, middle and last career: Risālah fī Aqsām al-‘Ulūm al-‘Aqliyyah, ‘Uyūn al-Ḥikmah, al-Madkhal, al-Ilāhiyyāt and Manṭiq al-Masyriqiyyīn. The author will conclude with three conclusions: (1) that Ibn Sina’s general conception of science is teleological in nature; that is, it puts the emphasize more on the aim of the sciences to perfect the human soul rather than on the essence of science in itself; (2) that the teleological conception gives Ibn Sina’s classification of the sciences a general structure by making man as the positive principle in the primary classification; and (3) that there is an incoherence in Ibn Sina’s classification in that the object of metaphysics is too general that it might cover the object of other theoretical sciences and even also the objects of practical sciences.